Near IR Photoconductive Detector Based on f-MWCNTs/Polythiophen Nanocomposite - Sadik, Hawraa; Saleh, Wasan R.; Hadi, Naseer M. Hadi; Kadhum, Noon (Iraqi Journal of Science, 2022)
Carbon nanotubes are an ideal material for infrared applications due to theirexcellent electronic and photo electronic properties, suitable band gap, mechanicaland chemical stabilities. Functionalised multi-wall carbon nanotubes (f-MWCNTs)were incorporated into polythiophen (PTh) matrix by electro polymerizationmethod. f-MWCNTs/ PTh nanocomposit films were prepared with 5wt% and10wt% loading ratios of f-MWCNTs in the polymer matrix. The films are depositedon porous silicon nanosurfaces to fabricate photoconductive detectors work in thenear IR region. The detectors were illuminated by semiconductor laser diode withpeak wavelength of 808 nm radiation power of 300 mW. FTIR spectra assignmentsverify that the thiophene groups were successfully introduced into the carbonnanotubes. SEM images reflect that the electro polymerization process gives wellincorporated for the MWCNTs by PTh polymer. Characteristics of photodetectorwere improved after cooling the detector. Figure of merit showed a good IRradiation sensitivity and photo response, while the specific detectivity was in orderof 109 cm.Hz1/2/W and at for both MWCNTs loading ratios at forward bias voltage5 Volts. The rise time and fall time of the output signal are about 192 μs and 121μsrespectively which consider good values for these types of detectors.